ANALISIS RETURN ON ASSETS (ROA), LOAN TO DEPOSITS RATIO (LDR) DAN BEBAN OPERASIONAL PENDAPATAN OPERASIONAL (BOPO) UNTUK MENILAI KINERJA PERBANKAN PADA PT BANK RAKYAT INDONESIA (PERSERO) Tbk - Gea, Katarina Syukur Arniwati; Hulu, Perlindungan Faebuadodo; Zai, Kurniawan; Telaumbanua, Aferiaman (Universitas Nusa Cendana, 2024)
This study aims to analyze the financial performance of PT Bank Rakyat Indonesia (Persero) Tbk during the 2016-2020 period using Return on Assets (ROA), Loan to Deposit Ratio (LDR), and Operating Expenses to Operating Income (BOPO) as the main indicators. The data used is the annual financial reports of BRI, which are processed using a descriptive quantitative approach. The results show that BRI's ROA declined from 2.67% in 2016 to 1.29% in 2020, but remained above the minimum bank health threshold. The LDR fluctuated during this period, with the highest ratio at 89.5% in 2018, but it did not meet the healthy bank ratio standard. BOPO also decreased, yet it did not reach the expected efficiency level as per Bank Indonesia's standard. Overall, BRI demonstrated healthy asset productivity performance but requires operational efficiency and fund utilization improvements. This study recommends enhancing liquidity and operational efficiency to improve the bank's overall financial performance. Keywords: Financial Performance; Return On Assets, Loan to Deposit Ratio; Beban Operasional Pendapatan Operasional